First Steps Towards a University Social Network on Personal Learning Environments - Marín-Díaz, Verónica; Vazquez Martinez, Ana Isabel; McMullin, Karen Josephine (International Review of Research in Open and Distributed Learning, 2014)
The evolution of the media and the Internet in education today is an unquestionable reality. At the university level, the use of Web 2.0 tools has become increasingly visible in the new resources that professors have been incorporating both into the classroom and into their research, reinforcing the methodological renewal that the implementation of the EHEA has demanded. The aim of this article is to introduce DIPRO 2.0, an educational social network for university professors to develop their training in the area of personal learning environments through collaborative learning and production of knowledge.